2011
DOI: 10.1016/j.jep.2011.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the anti-inflammatory and antinociceptive activities and the mechanism of the action of Lippia gracilis essential oil

Abstract: Our results indicate that the essential oil from Lippia gracilis produces an antinociceptive effect that could be potentially mediated by cholinergic receptors and the nitric oxide pathway. Our data also suggest that the anti-inflammatory activity caused by EO exposure occurs through inhibition of nitric oxide and PGE2 production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 42 publications
0
26
0
5
Order By: Relevance
“…Apesar dos vários relatos na literatura sobre a importância medicinal, bioquímica e ornamental das diversas espécies do gênero Lippia (Compadre et al, 1986;Valentin et al, 1995;Pascual et al, 2001;Costa et al, 2002;Hennebelle et al, 2008;Guilhon et al, 2011), ainda há escassez de estudos direcionados à propagação vegetativa, especialmente quanto ao melhor tipo de propágulo e substrato para algumas espé-cies, como é o caso da L. gracilis.…”
Section: R G Santos Et Alunclassified
“…Apesar dos vários relatos na literatura sobre a importância medicinal, bioquímica e ornamental das diversas espécies do gênero Lippia (Compadre et al, 1986;Valentin et al, 1995;Pascual et al, 2001;Costa et al, 2002;Hennebelle et al, 2008;Guilhon et al, 2011), ainda há escassez de estudos direcionados à propagação vegetativa, especialmente quanto ao melhor tipo de propágulo e substrato para algumas espé-cies, como é o caso da L. gracilis.…”
Section: R G Santos Et Alunclassified
“…Mice were used according to the method previously reported 42,43 . The doses and the routes of administration are provided in Section 2.5.1.…”
Section: Acetic Acid-induced Vascular Permeabilitymentioning
confidence: 99%
“…This test was performed in order to measure the latency of the response 42,43 . A glass cylinder was placed on a hotplate with adjustable temperature.…”
Section: Hot Plate Testmentioning
confidence: 99%
“…The nociceptive response in the acetic acid-induced abdominal constriction assay arises from synthesis of prostaglandins by the action of the constitutively expressed enzyme cyclooxygenase-2 (COX-2), which leads to hyperalgesia and pain (Berkenkopf and Weichmann 1988;Ballou et al 2000). Terpenes, the major constituent of BPEOs, possess numerous pharmacological and therapeutic properties and exert antinociceptive and anti-inflammatory effects (Mendes et al 2010;Guilhon et al 2011). Previous studies demonstrated analgesic activity for p-cymene (Illouz and Delbarre 1964;Duke et al 2002) and anti-inflammatory activity for γ-terpinene (Duke et al 2002;Milde et al 2004).…”
Section: Discussionmentioning
confidence: 99%